Determinan Motivasi Kerja Tenaga Kesehatan Pegawai Pemerintah Non Pegawai Negeri (PPNPN) di Rumah Sakit Angkatan Laut Dr Mintohardjo - Raharja, Hari; Kusumastuti, Istiana (MPI Press, 2021)
Introduction: Raising and maintaining work motivation isabsolutely done by every organization is a management ofhuman resources (HR), including HR for health workers in conducting health services. Objectives: The purpose of the study was to determine therelationship of the work environment, compensation andwork training with work motivation of PPNPN healthworkers in Dr.Mintohardjo Rumkital in 2020.Method: The design of this study was quantitative crosssectional, with a sample of 105 respondents. Data analysiswas performed univariately and bivariately with SpearmanCorrelation’s Analysis.Result: The results show there is a relationship between thework environment (p-value = 0.000 and r = 0.628),compensation (p-value = 0.000 and r = 0.427), and jobtraining (p-value = 0.000 and r = 0.504) with workmotivation of PPNPN health workers in Dr.MintohardjoRumkital in 2020.Conclution: Dr.Mintohardjo's Rumkital can increase themotivation of PPNPN health workers by increasing the safetyof the work environment, providing compensation tailored tothe workload and adjusting the type of work training to theproblems faced by health workers so that health services canbe improved and reducing the turnover rate ofDr.Mintohardjo's PPNPN Rumkital health workers.